2011
DOI: 10.1186/1748-717x-6-92
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate in nasopharyngeal carcinoma improved by high caseload volume: a nationwide population-based study in Taiwan

Abstract: BackgroundPositive correlation between caseload and outcome has previously been validated for several procedures and cancer treatments. However, there is no information linking caseload and outcome of nasopharyngeal carcinoma (NPC) treatment. We used nationwide population-based data to examine the association between physician case volume and survival rates of patients with NPC.MethodsBetween 1998 and 2000, a total of 1225 patients were identified from the Taiwan National Health Insurance Research Database. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…There were no disagreements between the 2 independent reviewers at this stage. This left 17 studies included in the systematic review (Figure ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no disagreements between the 2 independent reviewers at this stage. This left 17 studies included in the systematic review (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Sharma et al assessed all major head and neck cancer subsites except for the salivary gland. The remaining 13 studies focused on a single subsite; 4 studied the larynx, 2 the oropharynx, 4 the oral cavity, 1 the neck lymph nodes, and 2 the nasopharynx . Ten of these studies were from the United States, 6 from Taiwan, and 1 from New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…Propensity score stratification was applied to replace the wide host of confounding factors that may be present in an observational study with a variable of these factors [27-30]. To derive the propensity score in this study, patient characteristics were entered into a logistic regression model predicting selection for different category of the age groups.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, where patients reside and the level of hospital they visit may also affect physician caseload, a possible proxy for experience. Lee et al showed that NPC patients who were treated by high caseload volume physicians had a lower risk of death and were more likely to have greater survival [29]. Academic medical centers, which have more resources and a greater number of cases, are more likely to offer high-resolution MRI or positron emission tomography (PET) scan for tumor staging, IMRT with or without chemotherapy for radiotherapy and have physicians with high caseload volumes.…”
Section: Discussionmentioning
confidence: 99%